Karakteristik Nilai Kuat Tekan Bebas Tanahan Lempung Terhadap Perubahan Kadar Air Dan Tebal Lapisan Pemadat - Fikri Hidayat; Soewignjo Agus Nugroho; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Cohesive soil is a type of soil which is requiring a special handling. Clay as a soft soil has bad characteristic, so it needs to be improved in term of stability and bearing capacity. In Indonesia, there are many buildings and civil construction which have been damaged because they were built on expansive clays. For example, in the field we often find bumpy road pavement. This is happened due to poor bearing capacity of the subgrade which contains expansive clays. The aim of this research is to obtain significant factors that influence the UCS value and shape of the crack due to variations in density, moisture content and thickness of the compacted layer. Density variation used was amount of compaction energy. Variations in moisture content were 2% under OMC (OMC-), optimum moisture content (OMC) and 3% above OMC (OMC +). The thickness of the layers was controlled by the weight of the soil of each compaction layer. Moisture content variation results showed that the soil with the moisture content of OMC has largest UCS value. Test results from soil weight per layer showed that the lessest weight of soil, the highest of UCS value. This is because of the weight composition of each layer is evenly distributed. The most extreme collapse occurs in the second layer of each layer weight variation with the center of collapse in the middle layer.Keywords: Moisture content, UCS, soft clay, expansive soil